Sex Hormonal Profile in Men and Women with Epilepsy on Enzyme-Inducing Antiepileptic Drugs: A Case-Control Study - Manchukonda, Shivalaxmi; Jabeen, Shaik Afshan; Mohammed, Noorjahan; Cherian, Ajith; Chandran, Priscilla Abraham (International Journal of Epilepsy, 2018)
Introduction Prevalence of sexual and reproductive dysfunction in men and women with epilepsy (MWE and WWE) ranges from 20 to 60% in different studies. Epilepsy and antiepileptic drugs both contribute in varying degrees to the reproductive endocrine dysfunction.Aims and Objectives The aim of this study is to assess the alteration in sex hormone levels in MWE and WWE on enzyme-inducing antiepileptic drugs (EIAEDs).Materials and Methods This is a cross-sectional case-control study of 29 MWE and 26 WWE on EIAEDs. Control group were age- and sex-matched healthy volunteers. Serum sex hormones such as total testosterone (TT), dehydroepiandrosterone sulfate (DHEAS), estradiol (E2) and progesterone, gonadotropins such as luteinizing hormone (LH), follicular-stimulating hormone (FSH), and sex hormone–binding globulin (SHBG) levels were estimated. Free testosterone (FT) and bioactive testosterone (BAT) were calculated. Gonadal efficiency in men was estimated by TT/LH and in women by E2/SHBG and LH/FSH ratios.Results There was a significant decrease in TT/LH, FT, BAT, DHEAS, and progesterone along with a significant elevation of SHBG and E2 in MWE on EIAEDs. There was also significant elevation of gonadotropins such as LH, FSH, and prolactin (PRL) in MWE. A significant decrease in progesterone, DHEAS, and E2/SHBG along with a marked elevation in SHBG, LH, FSH, and PRL was found in WWE.Conclusion This study clearly demonstrates that EIAEDs have an adverse effect on reproductive health in both MWE and WWE.
Keywords: libido; testosterone; sex hormone–binding globulin; sexual dysfunction; androgen index; enzyme induction; antiepileptic drugs